Cohort profile: SCREEN-RA: design, methods and perspectives of a Swiss cohort study of first-degree relatives of patients with rheumatoid arthritis. Issue 7 (14th July 2021) - Gilbert, Benoit Thomas P; Lamacchia, Céline; Mongin, Denis; Lauper, Kim; Trunk, Eric; Studer, Olivia; Courvoisier, Delphine S; Rubbert-Roth, Andrea; Kyburz, Diego; Moeller, Burkhard; Finckh, Axel
Abstract : Purpose: Rheumatoid arthritis (RA) is an insidious autoimmune disease, with an immunological onset years before diagnosis. Early interventions in preclinical stages could prevent or minimise the progression towards irreversible joint damage. The SCREEN-RA cohort (Evaluation of a SCREENing strategy for Rheumatoid Arthritis) aims to characterise the preclinical stages of the disease, to identify environmental risk factors, and to discover or validate novel biomarkers predictive for RA development. Participants: SCREEN-RA includes an at-risk population for RA, namely first-degree relatives of patients with established RA. Findings to date: The cohort started in 2009 is composed of mostly asymptomatic healthy individuals (total n=1458, 7262 person-years), with a mean age of 44 years at enrolment, 74% female and 91% Caucasian ethnicity. During the study period, 16 participants have developed RA. All participants provide baseline serum, DNA and RNA samples, and in a subset, stool samples and oral examination are performed for microbiota assessment. At enrolment, 10% of participants had asymptomatic autoimmunity associated with RA (n=147), 10% presented 'clinically suspect arthralgias' (n=143) and 3% reported arthralgias in conjunction with autoimmunity or high genetic risk (n=51). Studies with this cohort have uncovered risk factors for RA development, such as female hormonal factors, poor oral health or intestinal dysbiosis. Future plans: Future directions include immunological and 'multiomics' approaches to discover new biological markers of progression towards RA, as well as testing preventive interventions in 'high-risk' population.